THE EXTENT OF INVOLVEMENT OF PRIVATE UNIVERSITIES’ STAKEHOLDERS IN THE PROCESS OF CHANGE IN TEACHER EDUCATION CURRICULUM IN KENYA - Adhiambo Amimo, Dr Catherine (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study explored the extent of involvement of private universities stakeholders in the process of change in teacher education curriculum. The respondents were School Deans, Heads of Departments, Teacher Trainees, and Teacher Educators. Theories Complexity and Planned Change guided the study. Purposive, cluster, convenience and snowball sampling methods were used. Research instruments comprised of questionnaires, letters of correspondences and daily news papers. Frequencies, means, standard deviations, Mann Whitney Wallis U test, and Spearman rho were used in data analysis. The study revealed that the stakeholders in private universities were not fully involved in the process of change – the Deans recording minimal ( = 2.29; SD= 1.21); and Teacher Trainees ( = 2.53, SD= .93) and Teacher Educators ( = 3.03, SD= .98) moderate involvements. Mann-Whitney U test (U=11774.500, p = .038) revealed a statistically significant difference between Teacher Educators ( = 2.76; SD = .13) and Teacher Trainees (2.46; SD= .06) involvements. Spearman rho correlation coefficients (r = 0.435; 0. 425; 0.561) between levels of Teacher Educators’ and Teacher Trainees’ involvements and ratings on management of change were significant (p < 0.05). The study recommends that for effective management of change in teacher education curriculum, the private university stake holders should be involved in the entire process of change, particularly in understanding the parameters and factors driving change.